Synthesis and activity of Helicobacter pylori urease and catalase at low pH. Issue 1 (January 1997) - Bauerfeind, P; Garner, R; Dunn, B E; Mobley, H L
Abstract : BACKGROUND: Helicobacter pylori produces large amounts of urease presumably to be prepared for the rare event of a sudden acid exposure. The hypothesis that H pylori is acid sensitive and protein production is inhibited by low pH was examined. METHODS: H pylori or its soluble enzymes were incubated buffered or unbuffered at a pH ranging from 2-7 in the presence of 5 mM urea for 30 minutes. After exposure, urease and catalase activities of whole cells, supernatants, and soluble enzyme preparations were measured at pH 6.8. Newly synthesised enzyme was quantified by immunoprecipitation of [35S]-methionine labelled protein. RESULTS: Exposure to buffer below pH 4 resulted in loss of intracellular urease activity. In soluble enzyme preparations and supernatant, no urease activity was measurable after incubation at pH < 5. In contrast, catalase in whole cells, supernatant, and soluble enzyme preparations remained active after exposure to pH > or = 3. Exposure below pH 5 inhibited synthesis of total protein including nascent urease and catalase. At pH 6 or 7, urease represented 10% of total protein, catalase 1.5%. Exposure of H pylori to unbuffered HCl (pH > 2) resulted in an immediate neutralisation; urease and catalase activities and synthesis were unchanged. CONCLUSION: Low surrounding pH reduces activity of urease and synthesis of nascent urease, catalase, and presumably of most other proteins. This suggests that H pylori is not acidophilic although it tolerates short-term exposure to low pH.